(untitled) (Passagens: Revista Internacional de História Política e Cultura Jurídica, 2026)
Sustainable Development Goal 12 that addresses sustainable consumption and production can be viewed as one of the pillars that can be used in managing environmental degradation and climate crisis. This research aims to examine how well legal actions can enhance sustainable consumption and production, which is presented in Sustainable Development Goal (SDG) 12. Its purpose is to add to the worldwide agenda of preventing climate change, which is seen as the magnifier of threats, by evaluating the use of legal structures to push the world. There is also secondary data, literature and legal framework and current situation through news incorporated in the research to obtain a glimpse of the difficulty and achievements of green legal measures implementation. The findings of the research indicate that the countries or regions, which have legal rules of sustainable consumption and production, clearly and successfully established and implemented, show positive results. Declines in resource consumption, generation of waste and greenhouse gases also experienced. To sum up, this paper highlights the critical importance of the legal interventions to the realization of SDG 12 and, consequently, tackling the overall issue of climate change. The results highlight that the legal structures can be instrumental in influencing consumer behavior, corporate activities, and creating a sustainable culture. The research can add value to the current body of knowledge in the sense that it offers policy and practical recommendations to policy makers, corporate citizens and other stakeholders on how to put effective legal frameworks and strategies into place to ensure sustainable consumption and production. The research offers a platform on how further studies can be conducted to understand how green legal frameworks have changed and how it has influenced in the reduction of climate change.